2022
DOI: 10.3390/toxics10090525
|View full text |Cite
|
Sign up to set email alerts
|

Microalgal Phycoremediation: A Glimpse into a Sustainable Environment

Abstract: Microalgae are continually exposed to heavy metals and metalloids (HMMs), which stifles their development and reproduction due to the resulting physiological and metabolic abnormalities, leading to lower crop productivity. They must thus change their way of adapting to survive in such a hostile environment without sacrificing their healthy growth, development, reproductive capacity, or survival. The mode of adaptation involves a complex relationship of signalling cascades that govern gene expression at the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 118 publications
1
8
0
Order By: Relevance
“…Additionally, a further classification of As is needed since organic As is far less toxic compared to inorganic arsenic species [ 106 ]. The accumulation of heavy metals showed a great variety between and within the same phyla as well as different and similar culture media, which is in accordance with the literature [ 107 , 108 ]. These data indicate that the accumulation of heavy metals does not only depend on the degree of heavy metal input during cultivation, which should, therefore, be carefully monitored and minimized.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, a further classification of As is needed since organic As is far less toxic compared to inorganic arsenic species [ 106 ]. The accumulation of heavy metals showed a great variety between and within the same phyla as well as different and similar culture media, which is in accordance with the literature [ 107 , 108 ]. These data indicate that the accumulation of heavy metals does not only depend on the degree of heavy metal input during cultivation, which should, therefore, be carefully monitored and minimized.…”
Section: Discussionsupporting
confidence: 91%
“…When two bacterial genes were co-expressed in Arabidopsis and cultivated in a medium containing sodium arsenate (125 M), the results were similar to those seen in above-ground biomass [103]. There is a lot of promise for improving heavy metals and metalloid resistance by altering genes to boost the production of metal chelation agents [104]. In A. thaliana and B. juncea, the constitutive expression of AtPCS1 boosted arsenate tolerance but did not increase shoot growth.…”
Section: Recent Biotechnological Approaches For Potential Phytoremedi...mentioning
confidence: 62%
“…Efflux is an important process for algae to detoxify heavy metals. ,, To simulate the efflux and desorption of Hg from algae cells with high levels of Hg into ambient water with low levels of Hg, CH, and CD exposed to 199 IHg and 201 MeHg for 24 h were resuspended in N-, P-, and Hg-free mediums. It was demonstrated that both IHg ab and MeHg ab on single cells decreased over time (Figures A and S18A), suggesting the efflux process from algae cells to ambient water.…”
Section: Resultsmentioning
confidence: 99%